Adsorption Properties of NF3 and N2O on Al- and Ga-Doped Graphene Surface: A Density Functional Theory Study - Qilin Yi; Gang Wei; Zhengqin Cao; Xiaoyu Wu; Yuanyuan Gao (Adsorption Science & Technology)
SF6/N2 gas mixture decomposition components can reflect the operation status inside GIS, and be used for fault diagnosis and monitoring inside GIS. NF3 and N2O are the characteristic decomposition components of SF6/N2 mixed gas. In order to find a potential gas sensitivity material for the detection of NF3 and N2O. This paper investigated the adsorption properties of NF3 and N2O on Al- and Ga- doped graphene monolayers based on density functional theory. Through the analysis of adsorption distance, charge transfer, adsorption energy, energy band structure, etc., the results indicated that the adsorption effect of Al- and Ga-doped graphene to NF3 and N2O are probably good, and these nanomaterials are potential to apply for the monitoring of GIS internal faults.